The pachytene checkpoint prevents accumulation and phosphorylation of the meiosis-specific transcription factor Ndt80 - Tung, Kuei-Shu (The National Academy of Sciences, 2000)
In budding yeast, many mutants defective in meiotic recombination and chromosome synapsis undergo checkpoint-mediated arrest at the pachytene stage of meiotic prophase. We recovered the NDT80 gene in a screen for genes whose overexpression bypasses the pachytene checkpoint. Ndt80 is a meiosis-specific transcription factor that promotes expression of genes required for exit from pachytene and entry into meiosis I. Herein, we show that the Ndt80 protein accumulates and is extensively phosphorylated during meiosis in wild type but not in cells arrested at the pachytene checkpoint. Our results indicate that inhibition of Ndt80 activity is one mechanism used to achieve pachytene arrest.